2016
DOI: 10.1175/jhm-d-16-0091.1
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Influences on Summertime Extreme Precipitation in the Northeastern United States

Abstract: Observations indicate that over the last few decades there has been a statistically significant increase in precipitation in the Northeastern United States and that this can be attributed to an increase in precipitation associated with extreme precipitation events. Here we use a state-of-the-art atmospheric reanalysis to examine such events in detail. Daily extreme precipitation events defined at the 75 and 95 percentile from gridded gauge observations are identified for a selected region within the Northeast.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 34 publications
6
43
0
Order By: Relevance
“…In contrast with early fall, we find a much smaller contribution (8%) to the annual 1996 EP shift from early summer (June-July) TCs. Collow et al (2016) detected no significant trend in summer EP events associated with TCs from 1985 to 2014. However, we emphasize that fall TCs are essential to explaining the total EP increase over the Northeast in our analysis.…”
Section: 1029/2017jd028136mentioning
confidence: 68%
“…In contrast with early fall, we find a much smaller contribution (8%) to the annual 1996 EP shift from early summer (June-July) TCs. Collow et al (2016) detected no significant trend in summer EP events associated with TCs from 1985 to 2014. However, we emphasize that fall TCs are essential to explaining the total EP increase over the Northeast in our analysis.…”
Section: 1029/2017jd028136mentioning
confidence: 68%
“…The synoptic pattern for the 19 August 2014 storm is similar to the 24 July 1990 storm documented by McCollum et al (). Previous studies highlight the role of cut‐off lows in producing extreme rainfall and flooding (e.g., Awan & Formayer, ; Knippertz & Martin, ; Marquardt Collow et al, ; Pinheiro et al, ). At 0600 UTC on 19 August, a strong upper‐level trough extended from −130°E to −110°E longitude at 500 hPa and extended toward 30°N latitude, with the 5,820 m contour cut‐off from the main circulation (Figure a).…”
Section: Overview Of the 19 August 2014 Stormmentioning
confidence: 99%
“…Note that color bars cover different ranges contribution to 1-h AMP is weaker and falls within the confidence range and is thus proportionate to the jet stream frequency. In the rest of the US, the jet stream contribution to 1-h AMP is nominal as precipitation extremes in these areas are generally set when other extra-tropical frontal systems (Marquardt Collow et al 2016), tropical cyclones (Knight and Davis 2009;Kunkel et al 2010), meso-scale convective systems (Kunkel et al 2012) or purely localized convective processes transit over the region.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, meso-scale convective processes responsible for heavy precipitation rates are often connected with large-scale vertical velocity and moisture convergence ) associated with synoptic-scale patterns . Previous studies have shown that daily or multi-day precipitation extremes in the US are often coincident with atmospheric rivers [e.g., (Dettinger et al 2011;Rutz et al 2014)] or extra-tropical cyclones [e.g., Agel et al (2015)] embedded within upperlevel dynamics such as the jet stream (Pfahl and Wernli 2012) and cutoff upper-level low pressure systems (Abatzoglou 2016;Marquardt Collow et al 2016). It is thus of interest to better understand the contribution of midlatitude circulation patterns to precipitation extremes on sub-daily timescales, and how this contribution varies geographically.…”
Section: Introductionmentioning
confidence: 99%